English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-03-22 16:15:24 · 10 answers · asked by MJ Boulevard 3 in Science & Mathematics Mathematics

10 answers

Y = 12

2007-03-22 16:18:52 · answer #1 · answered by Anonymous · 0 0

Take 3x=12 and solve for x by dividing by 3 on both sides. You get x=12/3 = 4. Then plug x=4 into y=3x. You get y=3(4)=12.

:-)

2007-03-22 16:19:54 · answer #2 · answered by darin2z 3 · 0 0

This makes a chain, see:

y=3x=12 --> y=12

2007-03-22 16:18:41 · answer #3 · answered by Anonymous · 0 0

Y=12

3x=12
divide both sides of the equation by 3 so x=4
plug that into the equation and solve for y
y= 3x
y= 3(4) and therefore
y=12

2007-03-22 16:34:31 · answer #4 · answered by passion2share 4 · 1 0

12
It's the substitution principle. Since y = 3x, y can replace 3x in the second equation, leaving you with y = 12.

2007-03-22 16:18:56 · answer #5 · answered by jenh42002 7 · 0 0

y is 12, did you mean what is x? x is 4

2007-03-22 16:25:44 · answer #6 · answered by Anonymous · 0 0

Use the identity property: If a = b and b = c, then a = c.

y = 12

2007-03-22 16:19:10 · answer #7 · answered by yanksfan 2 · 0 0

36

2007-03-22 16:19:57 · answer #8 · answered by Justina 3 · 0 2

y =3x
12=3x
both equal, so
y=12

2007-03-22 16:29:17 · answer #9 · answered by anbaijiao 2 · 0 0

You think you need help!!?? I need help. Help for my despair.

2007-03-22 16:26:14 · answer #10 · answered by OR1234 7 · 0 0

fedest.com, questions and answers